Inovação aplicada à educação no Brasil: manual Smart Law de ensino jurídico gamificado - JESUS, Jéssica Silva de (2022)
The main object of this paper is to present the constitution of a Gamified Legal Teaching Manual called: Smart Law, which can be replicated in different contexts, based on the use of gamification elements to carry out immersions and experiences focused on share legal knowledge, in an accessible and uncomplicated way. For the implementation of the Manual, the starting point is the realization of teaching events, in which the experience of gamification and its main elements are applied to legal education Thus, the basic elements of gamification make up an itinerary capable of collaborating in the construction of problem solving in the most diverse areas of knowledge. And among these action possibilities, the application of gamification to legal education stands out, under the terms of the Smart Law Manual.